Voices from the Second Republic of South Vietnam (1967-1975) - Taylor, Keith Weller (Studies on Southeast Asia ;, 2015)
The Republic of (South) Vietnam is commonly viewed as a unified entity throughout the two decades (1955-75) during which the United States was its main ally. However, domestic politics during that time followed a dynamic trajectory from authoritarianism to chaos to a relatively stable experiment in parliamentary democracy. The stereotype of South Vietnam that appears in most writings, both academic and popular, focuses on the first two periods to portray a caricature of a corrupt, unstable dictatorship and ignores what was achieved during the last eight years. The essays in Voices from the Second Republic of South Vietnam (1967-1975) come from those who strove to build a constitutional structure of representative government during a war for survival with a totalitarian state. Those committed to realizing a noncommunist Vietnamese future placed their hopes in the Second Republic, fought for it, and worked for its success. This book is a step in making their stories known.